Marsena Rudolph Patrick journals - Patrick, Marsena Rudolph, 1811-1888.
Journals kept by Patrick while serving in the Union Army. Documents his role in the 2nd Battle of Bull Run, Va., (1862); the Maryland Campaign (1862); the Battle of Gettysburg, Pa., (1863); operations along the Rapidan River, Va., (1863); Battle of Cold Harbor, Va., (1864); seige of Petersburg, Va., (1864-1865); and the entry of Union troops into Richmond, Va. Discusses the operations of the U.S. Army of the Potomac, Ambrose Everett Burnside, Ulysses S. Grant, Joseph Hooker, Abraham Lincoln, George Brinton McClellan, George Gordon Meade, and Edwin McMasters Stanton.
Army officer and agriculturalist.
Collection material in English.
Keywords: Burnside, Ambrose Everett, -- 1824-1881.; Grant, Ulysses S. -- 1822-1885.; Hooker, Joseph, -- 1814-1879.; Lincoln, Abraham, -- 1809-1865.; McClellan, George Brinton, -- 1826-1885.; Meade, George Gordon, -- 1815-1872.; Stanton, Edwin McMasters, -- 1814-1869.; United States. -- Army -- Officers; United States. -- Army of the Potomac; Bull Run, 2nd Battle of, Va., 1862.; Cold Harbor, Battle of, Va., 1864.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Maryland Campaign, 1862.; Maryland -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Siege, 1864-1865.; Rapidan River (Va.) -- History; Richmond (Va.) -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Agriculturists; Army officers